Analisis Materi Bahasa Inggris Sebagai Pendukung Kurikulum Tematik di Kelas V SD 1 Jepang Kabupaten Kudus - Rieke Dwi Wulandari; Muhammad Arief Budiman; Fine Reffiane (STKIP Andi Matappa Pangkep, 2022)
This study aims to determine whether there is a relationship between the English language material and the thematic learning material and what are the similarities and differences between the English language material and the thematic learning material. This type of research is a qualitative research, the data in the study were obtained through interviews with principals, English teachers, students, parents, observation sheets, and documentation. The results of the research that has been carried out are that English material can support thematic learning of class V. The similarity between English material and class V thematic material lies in the subject or topic where English material and thematic material usually contain vocabulary related to events. as well as daily activities. The difference between English material and thematic material lies in the presentation of the material because the presentation of English material usually only contains an introduction to vocabulary related to simple things in everyday life. While the presentation of material in thematic learning which consists of themes and subthemes is usually presented in detail and is more complex.